PROBLEMATIKA SEGMENTASI DALAM MULTIKULTUR PADA MASYARAKAT HINDU BALI - I Putu Suardipa (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
The State of Indonesia is a country that has a diversity of religions and beliefs, tribes,numbers and distribution of the number and distribution of the island, the language so that thecountry of Indonesia is referred to as a multicultural country. Bali as one of the areas that existin Indonesia in particular has a diversity of cultural segmentation both in terms of religion,dresta, lifestyle that is almost different in each region. The diversity makes them have a thickmulticultural character that includes the beliefs, ideas, worldviews, policies, attitudes and actionsof a pluralistic society in terms of ethnicity, culture, religion etc., but has the aspiration todevelop the same spirit of kinship and has the pride to defend the plurality. segmentation culturethat emerged in the community demands a level of gap that leads to social problems.Multiculturalism in this Balinese society provides a new perspective in examining a variety ofsocial and different life patterns in every region in Bali, through multicultural studies make theBalinese society civilized in a social system intact to build a harmonious, peaceful, safe, tolerant,mutual life respect, cooperate and cooperate in the framework of unity and unity of the wholenation.